Implementation of Bacteria Isolate as a Fertilizer and Bioinsecticide Agent for the Mealybug - Slamet Santosa; Umi Fatmawati (Universitas Muhammadiyah Surakarta, 2023)
This research about the implementation of bacteria in papaya plantation soil in Kebumen that has been isolated and characterized and purified. This study aims to determine the potential of local isolate bacteria from papaya agricultural soil: 1). as PGPR bacteria or fertilizing bacteria for chili, eggplant and tomato plants and 2) as a natural bioinsecticide. mealybugs on papaya plants. The samples used were bacteria from the preliminary isolation that had been carried out, namely from the genera Bacillus, Pseudomonas, Erwinia, Exyguobacterium, Serratia, Stenotropomonas, and Acinetobacter. The study was conducted using 50 stems of each plant. Bioinsecticides are applied to papaya trees that are attacked by mealybugs. Measurement of plant growth was measured at 7 days and 30 days after planting. As for bioinsecticides, spraying was carried out 3 times. The results of the study can be concluded in the form of the implementation of bacteria as PGPR which can increase the growth of cayenne pepper (Capsicum frutescens), purple eggplant (Solanum melongena L) and tomato (Solanum lycopersicum Mill) and can be used as a bioinsecticide to reduce mealybugs (Paracoccus marginatus) on papaya plants (Carica papaya L.)